Traditional Uses of Medicinal Plants at Badami Taluk, Karnataka : A Recent Study - A. A. Topalakatti (New Horizons in Medicine and Medical Research Vol. 8, 2022)
Since the Vedic time, local vaidhyas have had a traditional understanding of medicinal plants and their usefulness in local health care. In phytochemical research, screening medicinal plants has become a potential source of bio-dynamic chemicals with therapeutic utility. One method of capturing this corpus of knowledge is ethnobotanical documentation. As a result, traditional practitioners in Badami taluk of Bagalkot district conducted a survey of medicinal plants and their traditional applications. Badami taluk has a long history of medicinal plants dating back to the Chalukyan period.